Public participation in coping with floods in Pak Khware subdistrict, Mueang Sukhothai district, Sukhothai province - Meesiripan, Supawit; wongwatthanaphong, kampanart (Journal of Modern Learning Development, 2022)
The objectives of this research were 1) to study the level of people's participation in flood coping, 2) to compare personal factors for people's participation in flood coping, and 3) to propose a guideline. carry out flood prevention Conducted in accordance with the integrated research methodology. during quantitative research A survey study was used, a questionnaire with 363 people representing households, obtained by substituting the values ​​in the Yamane formula. The data were analyzed by using statistics such as frequency, percentage, mean, standard deviation. and t-test and F-test by One Way ANOVA and qualitative research. It consists of in-depth interviews with 5 key informants using content analysis and interpretation techniques. The results of the research showed that 1) people's participation in flood response Overall, it was at a high level. 2) Comparison found that people with different personal factors had opinions on people's participation in flood coping. no different Therefore, the hypothesis was rejected. 3) Flood prevention action guidelines found that flood prevention actions in Pak Khwae sub-district were prevention and mitigation of impacts preparedness of sub-district service organizations and peopleEmergency/Flood Disaster Management and Appropriate Post Disaster Management.